ENTERPRISE RISK MANAGEMENT ON FIRM VALUE : EMPIRICAL STUDY ON MANUFACTURING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Dinarossi Utami; Sulastri Sulastri; Moh. Adam; Yuliani Yuliani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Enterprise risk management (ERM) is being adopted by many firms globally and the value relevance of enterprise risk management is scarce. The purpose of this study was to determine the impact of enterprise risk management on firm value for companies on the Indonesia Stock Exchange. This study is conducted using a sample of manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2020. The findings indicate a significant correlation between enterprise risk management and firm value, indicating that enterprise risk management significantly contributes to firm value. These findings may be used to develop and shape enterprise risk management policy frameworks for firms and countries. The study provides new insights, from an Indonesian emerging market context on the value effects of enterprise risk management. Nonetheless, this study found that companies with larger and international samples may improve future studies. Keywords: Corporate Risk, Enterprise risk management, Firm Value.